Assessing the phototransformation of diclofenac, clofibric acid and naproxen in surface waters: Model predictions and comparison with field data. (15th November 2016) - Avetta, Paola; Fabbri, Debora; Minella, Marco; Brigante, Marcello; Maurino, Valter; Minero, Claudio; Pazzi, Marco; Vione, Davide
Abstract: Phototransformation is important for the fate in surface waters of the pharmaceuticals diclofenac (DIC) and naproxen (NAP) and for clofibric acid (CLO), a metabolite of the drug clofibrate. The goal of this paper is to provide an overview of the prevailing photochemical processes, which these compounds undergo in the different conditions found in freshwater environments. The modelled photochemical half-life times of NAP and DIC range from a few days to some months, depending on water conditions (chemistry and depth) and on the season. The model indicates that direct photolysis is the dominant degradation pathway of DIC and NAP in sunlit surface waters, and potentially toxic cyclic amides were detected as intermediates of DIC direct phototransformation. With modelled half-life times in the month-year range, CLO is predicted to be more photostable than DIC or NAP and to be degraded mainly by reaction with the OH radical and with the triplet states of chromophoric dissolved organic matter ( 3 CDOM*). The CLO intermediates arising from these processes and detected in this study (hydroquinone and 4-chlorophenol) are, respectively, a chronic toxicant to aquatic organisms and a possible carcinogen for humans. Hydroquinone is formed with only ∼5% yield upon CLO triplet-sensitised transformation, but it is highly toxic for algae and crustaceans. In contrast, the formation yield of 4-chlorophenol reaches ∼50% upon triplet sensitisation and ∼10% by · OH reaction. The comparison of model predictions with field data from a previous study yielded a very good agreement in the case of DIC and, when using 4-carboxybenzophenone as proxy for triplet sensitisation by CDOM, a good agreement was found for CLO as well. In the case of NAP, the comparison with field data suggests that its direct photolysis quantum yield approaches or even falls below the lower range of literature values. Graphical abstract: Highlights: Photochemical half-life times are predicted for three pharmaceuticals. Clofibric acid (CLO) is more photostable than diclofenac (DIC) and naproxen (NAP). Main reactions are direct photolysis (DIC and NAP) and indirect photolysis (CLO). Indirect photoreactions would mainly involve hydroxyl radicals and triplet states. Potentially harmful photoinduced intermediates could be formed from DIC and CLO.